Determination of multi‐pesticide residue in tobacco using multi‐walled carbon nanotubes as a reversed‐dispersive solid‐phase extraction sorbent. Issue 11 (27th April 2015) - Yu, Fei; Chen, Li; Pan, Lining; Hu, Bin; Liu, Huimin
<x xml:space="preserve">Abstract</x> A multi‐pesticide residue determination method based on a modified QuEChERS (quick, easy, cheap, effective, rugged, and safe) method using multiwalled carbon nanotubes as reversed‐dispersive solid‐phase extraction material was validated in 37 representative pesticides in tobacco. Determination was performed using liquid chromatography with tandem mass spectrometry in multiple reaction monitoring mode. Three major types of tobacco leaf samples, namely, flue‐cured, burley, and oriental tobacco were studied and compared. Three factors (extraction time, external diameter, and amount of extraction material used) that could affect the performance of multi‐walled carbon nanotubes were investigated. Optimization of sample preparation and determination allowed recoveries between 70.8 and 114.8% for all 37 pesticides with < 20.0% relative standard deviations at three spiking levels of 20, 50, and 200 μg/kg. The limits of quantification and limits of detection for the 37 pesticides ranged within 0.46–28.57 and 0.14–8.57 μg/kg at a signal‐to‐noise ratio of 10 and 3, respectively.